DEN DANSKE PELSSEKTOR IND I DET 21. ÅRHUNDREDE STRUKTUR, UDVIKLING OG MARKEDER. - Hansen, H. (Tidsskrift for Landøkonomi, 2024)
DEN DANSKE PELSSEKTOR IND I DET 21. ÅRHUNDREDE STRUKTUR, UDVIKLING OG MARKEDER.